UNIT STRATOTYPES FOR GLOBAL STAGES: THE NEOGENE PERSPECTIVE - Hilgen F.; Zachariasse W.J.; Brinkhuis H. (My University, 2006)
Recent developments in integrated high-resolution stratigraphy and astronomical tuning of continuous deep marine successions invalidate arguments against the designation of unit stratotypes for global stages, the basic building blocks of the standard Global Chronostratigraphic Scale (GCS). For the late Neogene, Global Stratotype Section and Point (GSSP) sections may also serve as unit stratotypes, covering the interval from the base of a stage up to the level that-time-stratigraphically-correlates with the base of the next younger stage in a continuous and well-tuned deep marine succession. The added value of such sections as unit stratotype lies in the integrated high-resolution stratigraphy and astronomical tuning, which combined, provides an excellent age control with an unprecedented resolution, precision and accuracy within the entire stage. As such they form the backbone of the new integrated late Neogene time scale and provide the basis for reconstructing Earth's history. In this way a stage is also defined by its content and not only by its boundaries. Our unit stratotype concept strengthens the importance of time-rock units by allowing the introduction of astronomically defined chronozones as formal chronostratigraphic units, thereby arguing against the elimination of the dual classification of chronostratigraphy and geochronology. Extending this concept to older time intervals requires that well-tuned, continuous deep marine sections are employed, thus necessitating the employment of multiple hole (I)ODP sites for defining (remaining) stages and stage boundaries in at least the Cenozoic and Cretaceous and possibly the entire Mesozoic. Evidently the construction of the Geological Time Scale (including the GCS) should be based on the most appropriate sections available while, where possible, taking the historical concept of global stages into account. © 2005 Elsevier B.V. All rights reserved.
Keywords: CHRONOSTRATIGRAPHY; CHRONOZONE; GSSP; ORBITAL TUNING; STAGE; UNIT STRATOTYPE; Cenozoic::Neogene; Кайнозой::Неоген; Mesozoic::Cretaceous; Мезозой::Меловая